Teachers’ Strategies in Teaching Speaking at MAN 2 Padang - Utami EZ, Fany Tri; Amri, Zul (Journal of English Language Teaching, 2024)
Speaking is one of the language skills that students must master, even though it is not easy. Teacher must implement appropriate teaching strategies to overcome students’ speaking difficulties. This study aimed to find out the teachers' strategies in teaching speaking at MAN 2 Padang and the students’ perceptions of the strategies in teaching speaking. This research was descriptive research with a mixed approach that combines qualitative and quantitative data. The samples for this research were three English teachers and the students of three classes where the observations were carried out. The instrument were observation, interviews, and questionnaire. Observation and interview data were analyzed by activating data, making transcripts, and drawing conclusions. Quesinoer data was analyzed using Excel. The results of this research indicate that teacher A used live listening, drilling and chant, writing task, discussion, presentation, and outside-class speaking strategies. The students’ perceptions of Teacher A’s strategies were good with average perception results ≥76%. Teacher B uses recording and transcript, live listening, drilling, writing task, dialogue, role-play, and discussion strategies. The students’ perceptions of Teacher B’s strategies were quite good with average perception results ≤75%. Teacher C uses live listening, writing task, dialogue, role-play, discussion and debate, and presentation strategies. The students’ perceptions of Teacher C’s strategies were good with average perception results ≥76%. It can be concluded that the teachers at MAN 2 Padang use recording and transcript, live listening, drilling and chant, writing task, dialogue, role-play, discussion and debate, presentation, and outside-class speaking strategies in teaching speaking and students’ perceptions of the strategies were good.